Lamination of Spinal Cord Gray Matter in Goat Foetii - Maya, S. Krishnan; Chungath, J. J.; Harshan, K. R.; Ashok, N. (Indian Journal of Veterinary Anatomy, 2015)
Architectural organization of neurons in the laminae of spinal cord gray matter in goat was studied using 52 specimens of various ages. Tubular primordium, neural tube, started to differentiate into gray and white matter of the spinal cord from 48 days. Gray matter presented its horns, and the laminae started to appear by this age. Even though all the ten laminae could not be differentiated at this stage, the onset of lamination was indicated by the formation of nuclear aggregations in lamina IX of ventral horn. These aggregations became better defined towards the end of second month at the enlargements. By beginning of third month, the lamination was clear at lamina II (substantia gelatinosa), VII (intermedio-lateral nucleus) and IX (nuclear aggregations in ventral horn). Towards the end of third month, other laminae started to differentiate and became better differentiated by fourth month. Gray matter presented all the ten laminae towards the end of gestation.